ENHANCING SPEAKING SKILL THROUGH EXI (ENGLISH EXPRESSING OPINION) APPLICATION - Iin Baroroh Maarif; Khusni Fakhriyyah Fakhriyyah (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2022)
ABSTRACT This research aims at designing an English learning application which called EXI (English Expressing Opinion). This product consists of some materials and exercises which is appropriate and feasible to be studied for students. All materials in this product are based on senior high school Geade XI. The purpose of designing this product is to enhance students’ speaking skill. The research method used in this research is Research and Development. This development used ADDIE model which have several steps, those are; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The result of this research shows that both the media validation and the material validation are in “very good” category. The students’ responses of try out result also shows in “very good” category. By having those result, this EXI (English Expressing Opinion) application is feasible to be used as a supplementary learning media for students at grade XI. Furthermore this research can be used as reference to other researcher in developing English learning media in different level of students. Key words: EXI (English Expressing Opinion ), Learning Media, Speaking skill, Senior High School